Hormone-dependent activation and repression of microRNAs by the ecdysone receptor in the dengue vector mosquito Aedes aegypti - He, Ya-Zhou (Proc Natl Acad Sci U S A, 2021)
Female mosquitoes transmit numerous devastating human diseases because they require vertebrate blood meal for egg development. MicroRNAs (miRNAs) play critical roles across multiple reproductive processes in female Aedes aegypti mosquitoes. However, how miRNAs are controlled to coordinate their activity with the demands of mosquito reproduction remains largely unknown. We report that the ecdysone receptor (EcR)–mediated 20-hydroxyecdysone (20E) signaling regulates miRNA expression in female mosquitoes. EcR RNA-interference silencing linked to small RNA-sequencing analysis reveals that EcR not only activates but also represses miRNA expression in the female mosquito fat body, a functional analog of the vertebrate liver. EcR directly represses the expression of clustered miR-275 and miR-305 before blood feeding when the 20E titer is low, whereas it activates their expression in response to the increased 20E titer after a blood meal. Furthermore, we find that SMRTER, an insect analog of the vertebrate nuclear receptor corepressors SMRT and N-CoR, interacts with EcR in a 20E-sensitive manner and is required for EcR-mediated repression of miRNA expression in Ae. aegypti mosquitoes. In addition, we demonstrate that miR-275 and miR-305 directly target glutamate semialdehyde dehydrogenase and AAEL009899, respectively, to facilitate egg development. This study reveals a mechanism for how miRNAs are controlled by the 20E signaling pathway to coordinate their activity with the demands of mosquito reproduction.